Good decision vs. good results: outcome bias in the evaluation of financial agents [dataset] - König-Kersting, Christian; Pollmann, Monique; Potters, Jan; Trautmann, Stefan T. (Universität, 2020)
We document outcome bias in situations where an agent makes risky financial decisions for a principal. In three experiments, we show that the princ...
Gesehen am 11.11.2020
Keywords: Forschungsdaten; Datenbank